An unknown collection of music manuscripts from Otyń (Wartenberg) - Frankowski, Patryk; Mądry, Alina (Interdisciplinary Studies in Musicology, 2018)
The Museum of Musical Instruments in Poznan (a branch of the National Museum) is in possession of a very important collection of music manuscripts from the former Jesuit monastery in Otyń (Ger. Wartenberg), which was dissolved in 1776. The activities of this centre were associated primarily with the figure of Karol Reinach, the monastery’s last superior (from 1753). Reinach maintained friendly relations with Frederick II the Great, who was an ardent flautist, as we know, and visited Otyń from time to time. The Otyń manuscripts were bequeathed to the museum in 1947, along with three preserved instruments: a pair of kettledrums and a bass viola da gamba. At present, the collection of manuscripts from the Jesuit ensemble of Otyń contains fifty-six compositions, written between 1753 and 1768. Thirty-one pieces have fully certified provenance, reflected on the title pages of the manuscripts in the form of inscriptions, such as ‘pro Choro Residentiae Wartenbergensis’, and in the names of the Otyń transcribers. Twenty-two compositions were classified as belonging to the Jesuit collection on the basis of its inventory number, placed in the top right corner. Seventeen of the preserved manuscripts were provided with exact dates of origin (ten compositions were dated to the day, the other seven to a particular year). In these manuscripts, one can find compositions of the following types: offertoria, antiphons, Marian hymns (mostly arias), litanies, carols, a cantata, a dialogue and a sequence. All of them are vocal-instrumental. The lyrics were written in Latin and German, and their subject matter is mostly connected with the Marian cult (the antiphons Ave Regina Caelorum, Alma Redemptoris Mater and Regina Coeli Laetare\ the hymn Ave Maris Stella), Jesuit themes (a litany of St John Nepomucen, a prayer of St Francis Xavier, O Deus Amo ego te) and Christmas (carols). The well-known composers include Frantisek Xaver Brixi (1732-1771), Carl Ditters von Dittersdorf (1739-1799), Carl Heinrich Graun (1704-1759), Johann Adolph Hasse (1699-1783) and Karel Loos (1724-1772), and there are also the less well-known or nearly unknown, such as Carolus Gaebel [Gebel], F. Passelt [?], Joseph Rhodigez, Antonio Josepho Ronge (or Runge [?]), Francisco Rudolph and Wollmann. The continued examination of the collection will certainly reveal more details that are unknown or as yet barely identified. The research is due to be capped with the publication of a thematic catalogue of Otyń’s music manuscripts and their registration in the RISM database.